2007
DOI: 10.1086/520875
|View full text |Cite
|
Sign up to set email alerts
|

Hubble Space TelescopeSurvey of Interstellar12CO/13CO in the Solar Neighborhood

Abstract: We examine 20 diffuse and translucent Galactic sight lines and extract the column densities of the 12 CO and 13 CO isotopologues from their ultraviolet AYX absorption bands detected in archival Space Telescope Imaging Spectrograph data with k/Ák ! 46;000. Five more targets with Goddard High-Resolution Spectrograph data are added to the sample that more than doubles the number of sight lines with published Hubble Space Telescope observations of 13 CO. Most sight lines have 12 CO-to-13 CO isotopic ratios that ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
95
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(105 citation statements)
references
References 69 publications
(158 reference statements)
10
95
0
Order By: Relevance
“…The term in the denominator corrects from visual to FUV extinction. Note, that the elemental abundances of carbon show an elemental ratio (ER) of 67, close to the average ratio in the local ISM (Sheffer et al 2007). We computed 168 models.…”
Section: Model Parameter Gridmentioning
confidence: 55%
See 1 more Smart Citation
“…The term in the denominator corrects from visual to FUV extinction. Note, that the elemental abundances of carbon show an elemental ratio (ER) of 67, close to the average ratio in the local ISM (Sheffer et al 2007). We computed 168 models.…”
Section: Model Parameter Gridmentioning
confidence: 55%
“…Liszt (2007) to decline for higher column densities and a total CO column densities of a few 10 16 cm −2 from Galactic CO absorption and emission at 1.3 and 2.1 mm wavelengths for clouds with a total CO column density N(CO) ≤ 10 16 cm −2 . Sheffer et al (2007) showed, that UV data toward diffuse/translucent lines of sight can give 0.5…”
mentioning
confidence: 99%
“…Approximating again the partition function by Q(T ) ∼ kt/(hB) (Sect. 3.1.1) we have Q(163K) ≈ 62 and Q(103K) ≈ 39, and using the 12 CO to 13 CO isotopologic ratio of 69 (e.g., Sheffer et al 2007), the derived total CO column densities toward source n are ≈4.3 × 10 18 cm −2 and ≈6.7 × 10 18 cm −2 , of the same order as for the BN object. With the CO-to-H 2 conversion factor of 8 × 10 −5 , the corresponding H 2 column densities are 5.3 × 10 22 cm −2 and 8.4 × 10 22 cm −2 .…”
Section: Source N 321 Co Absorption and Emissionmentioning
confidence: 70%
“…12 CO and 13 CO need similar amounts of self-shielding to survive in a hostile interstellar environment. This favors the more abundant isotopologue (e.g., Sheffer et al 2007). For the Galaxy, such effects can be quantified.…”
Section: Chemical Fractionation and Isotope Selective Photodissociationmentioning
confidence: 99%